2022
DOI: 10.3390/foods11121703
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Knowledge and Acceptance of “Algae” as a Protein Alternative: A UK-Based Qualitative Study

Abstract: Overconsumption of meat has been recognised as a key contributing factor to the climate emergency. Algae (including macroalgae and microalgae) are a nutritious and sustainable food source that may be utilised as an alternative to animal-based proteins. However, little is known about the consumer awareness and acceptance of algae as a protein alternative. The aim of this qualitative study was to develop a rich and contextualised understanding of consumer beliefs about the use of algae in novel and innovative fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…Participants' percentage who was firmly interested to use three modes of Spirulina-based products was 88%, 86.5%, and 91.7% for Spirulina tablets, powder, and food supplements respectively. In accordance with previous research, it can be said that people are influenced by several product attributes, including perceived edibility, healthiness, sustainability, and affordability 62) . In this regard, the outcomes attained here seem consistent.…”
Section: Willingness To Accept and Willingness To Paysupporting
confidence: 87%
“…Participants' percentage who was firmly interested to use three modes of Spirulina-based products was 88%, 86.5%, and 91.7% for Spirulina tablets, powder, and food supplements respectively. In accordance with previous research, it can be said that people are influenced by several product attributes, including perceived edibility, healthiness, sustainability, and affordability 62) . In this regard, the outcomes attained here seem consistent.…”
Section: Willingness To Accept and Willingness To Paysupporting
confidence: 87%
“…They identified four consumer cluster profiles: "Enthusiast", "Cautiously Curious", "Currently Waiting", and "Uninterested" [346]. Similarly, Mellor et al [347] stated that British consumers had limited knowledge of algae as a food source but were willing to try them, and the anticipated acceptance of algae was influenced by the perceived novelty, edibility, healthiness, sustainability, and affordability. Weickert et al [348] investigated the consumer acceptance of microalgal cultivation technology.…”
Section: Algal Proteinsmentioning
confidence: 99%
“…Lafarga et al [349] reported that Spanish consumers considered microalgae sustainable, nutritious, and safe, while the main reasons for low consumption were lack of knowledge and lack of habit. In general, increasing the consumer awareness and knowledge of algae and algal proteins could increase the market shares of algal products [346,347,349]. However, flavor (aromatics and basic tastes) remains a critical barrier.…”
Section: Algal Proteinsmentioning
confidence: 99%
“…20 Some of the commonly cultivated algal species are rich in protein (47-70% of dry biomass) and essential amino acids. 21 However, similar to most plant proteins, algae protein has a relatively low solubility at acidic pH values, particularly near their isoelectric points compared with the animal-based ones. Schwenzfeier et al 22 reported that the acidic environment (pH of 3.0-5.0) reduced the solubility of protein extracted from green microalgae Tetraselmis sp.…”
Section: Introductionmentioning
confidence: 99%